OPTIMISATION OF THE BENEFICIATION PROCESS OF CHROMITE SAND TO PRODUCE RAW MATERIAL FOR RAPID SAND-CASTING PURPOSES - Tshabalala, Neo; Nyembwe, Kasongo (The South African Journal of Industrial Engineering, 2024)
This study focuses on optimising the beneficiation process of South African chromite sand for use in rapid sand-casting applications, particularly for three-dimensional printing (3DP). South Africa’s vast chromite reserves provide a unique opportunity to produce high-quality chromite sand that is tailored for modern manufacturing needs. By identifying critical steps in the beneficiation process, such as crushing, grinding, and impurity removal, this research aims to enhance the quality and consistency of the final product. The optimised chromite sand demonstrates improved thermal stability and particle distribution, making it suitable for the stringent requirements of 3DP in sand casting.